FoT-PDS: A User-Centric Paradigm for Privacy-Preserving IoT - Pinto, George P.; Prazeres, Cássio V. S. (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2026)
The adoption of IoT technologies has amplified concerns regarding personal data privacy, as the continuous collection and processing of personal data expose users to structural privacy risks, including identification, localization and tracking, profiling, and linkage. Current IoT platforms primarily rely on service-centric models, offering limited user control, transparency, and support for informed consent throughout the data lifecycle. This thesis addresses these limitations by proposing FoT-PDS, a user-centric privacy-preserving IoT paradigm that integrates Personal Data Stores and the Fog of Things. The paradigm reassigns data control from service providers to users, enabling decentralized personal data management, fine-grained access control, transparency, and explicit consent. A central component of the paradigm is an AI-assisted consent mechanism that supports users in making informed consent decisions by analyzing their own data. The mechanism leverages clustering methods to evaluate potential profiling risks from users’ personal data. FoT-PDS was implemented and evaluated through both technical and empirical studies. Technical experiments demonstrate the feasibility of the consent mechanism under typical fog and IoT constraints, while a user-centric empirical study shows that the paradigm improves perceived data control, transparency, and privacy awareness. Trust is indirectly supported through increased privacy awareness, highlighting its mediating role in privacy-preserving IoT systems. These insights provide evidence that FoT-PDS can effectively mitigate privacy risks in IoT environments.